2013
DOI: 10.1002/hed.23350
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates and prognostic factors for infiltrating salivary duct carcinoma: Analysis of 228 cases from the Surveillance, Epidemiology, and End Results database

Abstract: Background The survival rates and prognostic factors for salivary duct carcinoma (SDC) are not clear. Methods Survival estimates and prognostic factors were evaluated for 228 patients with SDC identified from the Surveillance, Epidemiology, and End Results (SEER) database. Results Median overall survival (OS) duration for patients with SDC was 79 months and 5-year disease-specific survival (DSS) rate was 64%. Among patients with SDC with lymph node involvement, larger primary tumor size (>3 cm) was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
177
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(206 citation statements)
references
References 24 publications
15
177
8
1
Order By: Relevance
“…SDC is most frequently seen in men aged 50 or older [4, 6, 16, 18, 19] and is one of the more rare malignant salivary tumors. In one series of all salivary gland cancers during a 5-year period in Finland, it was estimated that 4–6% were SDC [20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SDC is most frequently seen in men aged 50 or older [4, 6, 16, 18, 19] and is one of the more rare malignant salivary tumors. In one series of all salivary gland cancers during a 5-year period in Finland, it was estimated that 4–6% were SDC [20].…”
Section: Introductionmentioning
confidence: 99%
“…In one series of all salivary gland cancers during a 5-year period in Finland, it was estimated that 4–6% were SDC [20]. A review of the SEER Medicare Database found that SDC comprised 1.8% of all major salivary gland cancers included in the database [19]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations